PREDATION OF PSOMOPHIS GENIMACULATUS (BOETTGER, 1885) (SQUAMATA – COLUBRIDAE) BY GUIRA GUIRA (GMELIN, 1788) (CUCULIFORMES – CUCULIDAE) IN THE SOUTHERN PANTANAL, BRAZIL (REMUNOM, 2026)
Guira guira (Gmelin, 1788) is a bird widely distributed throughout South America, characterized by diurnal habits and a predominantly carnivorous generalist diet, mainly composed of arthropods, although the consumption of small vertebrates has also been occasionally reported. In this study, we document the first record of predation by Guira guira on a juvenile Psomophis genimaculatus in the southern Pantanal. The event was observed on November 3, 2025, in the municipality of Aquidauana, Mato Grosso do Sul, Brazil, and involved an adult individual capturing and completely ingesting the snake, even in the presence of anthropogenic disturbance and adverse environmental conditions. During the observation, a second individual exhibited typical food-begging behavior, suggesting a parental care context. This record highlights the species’ ability to manipulate and consume relatively large vertebrate prey, reinforcing its opportunistic and generalist nature, as well as its high behavioral plasticity. Furthermore, the predation of a juvenile snake, potentially rich in energetic reserves, may represent an efficient strategy to maximize energy intake during periods of increased metabolic demand. This study expands current knowledge of the trophic ecology of G. guira and contributes to the understanding of predator–prey interactions in the Pantanal, emphasizing the species’ role as a potentially important predator within local herpetofaunal communities.